2015
DOI: 10.1016/j.eats.2015.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Knee Osteochondral Lesions With Ultrasound Imaging

Abstract: Evaluation of articular cartilage and subchondral bone is essential in the diagnosis of joint diseases and injuries. Interobserver and intraobserver reproducibilities of arthroscopic grading are only poor to moderate. Thus, for quantitative and objective evaluation of cartilage and subchondral bone, ultrasound arthroscopy (UA) has been introduced to clarify this dilemma. Assessment of the clinical feasibility of high-frequency ultrasonography (US) during 6 knee arthroscopies was conducted, and the surgical tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Surgeons frequently rely on postdebridement arthroscopic measurement of defects, and a variety of methods are commonly used to estimate size. Despite new imaging modalities, many surgeons believe that use of measuring devices during arthroscopic surgery is necessary for achieving accurate lesion measurement 15,[25][26][27] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgeons frequently rely on postdebridement arthroscopic measurement of defects, and a variety of methods are commonly used to estimate size. Despite new imaging modalities, many surgeons believe that use of measuring devices during arthroscopic surgery is necessary for achieving accurate lesion measurement 15,[25][26][27] .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the gold standard for sizing cartilage defects of the knee has been the direct measurement of defect size during arthroscopic knee surgery, commonly based on post-debridement arthroscopic sizing. Novel sizing methods, such as ultrasound examination, have been introduced as clinically feasible mechanisms for the diagnosis of cartilage lesions at the time of arthroscopy, but direct visual measurement still remains the gold standard 15 . The reported accuracy of arthroscopic sizing of defects varies in the current literature 16 .…”
mentioning
confidence: 99%
“…Hacker 856 et al 14 and Trudel et al 15 demonstrated a histologybased approach to compare AC surface topography against reference points on the AC surface. Furthermore, evaluation of AC surface roughness has been determined from image information obtained by ultrasound microscopy, [16][17][18] intravascular ultrasound, 19,20 and optical coherence tomography (OCT). 21,22 The most common clinically used imaging modality to quantify topography of degeneration is magnetic resonance imaging (MRI).…”
mentioning
confidence: 99%
“…To demonstrate articular cartilage surface using computerized tomography arthrography is the best choice, magnetic resonance is imaging technique through which demonstration of all tissue can be achieved (Figure 3) [59]. The US is used for assessment of both chondral and subchondral tissue components [62].…”
Section: Osteochondral Defectmentioning
confidence: 99%